2002
DOI: 10.1002/gene.10098
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of split hand/foot malformation type I

Abstract: Split hand/foot malformation type I (SHFM1) disease locus maps to chromosome 7q21.3-q22, a region that includes the distal-less-related (dll) genes DLX5 and DLX6. However, incomplete penetrance, variable expressivity, segregation distortion, and syndromic association with other anomalies have so far prevented the identification of the SHFM1 gene(s) in man. Here we show that the targeted double inactivation of Dlx5 and Dlx6 in the mouse causes in homozygous mutant animals bilateral ectrodactyly with a severe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 20 publications
6
124
0
Order By: Relevance
“…Deletion of the coding and intergenic regions of Dlx5 and Dlx6 with a single targeting event in the mouse results in perinatal death and in a limb malformation reminiscent of the human ectrodactyly, Split Hand Foot Malformation type I (Merlo et al, 2002;Robledo et al, 2002). In this study, we describe the craniofacial lesion present in Dlx5/6 double mutant mice.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Deletion of the coding and intergenic regions of Dlx5 and Dlx6 with a single targeting event in the mouse results in perinatal death and in a limb malformation reminiscent of the human ectrodactyly, Split Hand Foot Malformation type I (Merlo et al, 2002;Robledo et al, 2002). In this study, we describe the craniofacial lesion present in Dlx5/6 double mutant mice.…”
Section: Introductionmentioning
confidence: 87%
“…We have deleted the coding and intergenic regions of Dlx5 and Dlx6 in the mouse with a single targeting event (Merlo et al, 2002). Homozygous mutant mice die shortly after birth.…”
Section: Generation Of Dlx5/6 Double Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 SHFM1 (MIM 183600) is associated with genomic lesions on chromosome 7q21 in a minimal region, which includes the distal-less-related homeogenes DLX5 and DLX6. 16,17 The double knockout of Dlx5 and Dlx6 (Dlx5/6 D-KO) in the mouse leads to ectrodactyly in the hindlimbs 18,19 with defective development of the middle portion of the AER. Dlx genes code for homeodomain transcription factor homologues to insect distal-less and play a key role in the control of appendage development.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous Dlx5 mutant mice exhibit multiple defects in craniofacial structures (Depew et al1999, Acampora et al 1999. It has been reported that homozygous Dlx5/Dlx6 double-knockout mice exhibit split hand/foot malformation (SHFM) phenotypes (Merlo et al 2002). To develop an systematic in vitro approach for the study of human imprinting loci, we have previously generated human monochromosomal hybrids, via microcell chromosome transfer, that contain a single human chromosome of defined parental origin (Kugoh et al 1999, Meguro et al 2001.…”
Section: Introductionmentioning
confidence: 99%